LincRNA00494 Suppresses Non-small Cell Lung Cancer Cell Proliferation by Regulating SRCIN1 Expression as a ceRNA - Dong, Jingsi; Li, Bingjie; Lin, Dan; Lu, Dan; Liu, Chang; Lu, Xingbing; Tang, Xiaojun; Li, Lu; Zhu, Daxing; Liu, Jiewei; Qiu, Xiaoming; Tian, Long; et al. (Frontiers in Oncology, 2020)
Background: Lung cancer is the most common malignant tumor worldwide. Accumulating results have shown that long non-coding RNAs (lncRNAs) play a key role in tumorigenesis. Patients and Methods: A total of 163 tumor tissues were collected from non-small cell lung cancer (NSCLC) patients from West China Hospital of Sichuan University. LincRNA00494 is a novel lncRNA, and its expression and biological effect in NSCLC were reported in this study. NSCLC cell lines were used in this study. Results:LincRNA00494 is mainly distributed in the cytoplasm. LincRNA00494 was downregulated in the tumor tissues compared with the adjacent non-tumor tissues. LincRNA00494 expression was positively correlated with SRCIN1 expression (R = 0.57, P < 0.05). Silencing of LincRNA00494 in the cell lines substantially decreased SRCIN1 expression at the mRNA and protein levels, whereas overexpression of LincRNA00494 enhanced the SRCIN1 levels. miR-150-3p significantly decreased the luciferase signals of LincRNA00494 and SRCIN1 reporters. After transfection with miR-150-3p mimics and miR-150-3p inhibitor, overexpression of LincRNA00494 decreased the proliferation of the H358 (36%) and H1299 (29%) cell lines compared with that of the control cells, as shown by CCK-8 assays, whereas silencing LincRNA00494 promoted the proliferation of the H358 (47%) and H1299 (35%) cells. Tumor growth from LincRNA00494-overexpressing xenografts was significantly decreased; additionally, LincRNA00494 silencing substantially increased tumor growth compared with that of the control cells. Conclusions: Functional experiments revealed that LincRNA00494 inhibited NSCLC cell proliferation, which might be related to the suppression of SRCIN1, a tumor suppressor gene, by acting as a decoy for miR-150-3p. The data showed that LincRNA00494 might have antineoplastic effects during NSCLC tumorigenesis through its role as a ceRNA.